Evidence-based Biomedical Informatics - Lovis, C. (Yearbook of Medical Informatics, 2013)
Objectives: An overview of current trends and achievements in building more evidence of using information sciences technologies in biomedical informatics.Methods: Extensive search using PubMed for published papers in this field in 2012. A selection process organized in three steps: a) identification and first selection of papers; b) international peer-review by at least 4 reviewers for each paper; c) final selection of five papers by the editorial board of the Yearbook based on the international reviewing results and a balanced coverage of the topics.Results: Synopsis of the articles selected for the IMIA Yearbook 2012 and an invited opinion paper written by leading scientists in this field.Conclusion: Evidence based health informatics is an important and ubiquitous trend in biomedical informatics. However, this research field has to be enhanced even further and, more importantly, achievements have to be put in practice.
Keywords: Evidence; biomedical informatics